Analisis Tindak Tutur Ilokusi pada Video “Siap UTBK 2023” dalam Playlist Ruangguru - Gita Bintang Aulia; Iko Meifarindra Anugari; Nesa Artika Dewi; Wafiqotul Azizah; Hilda Af’idatussofa; Asep Purwo Yudi Utomo; Anggit Wicaksono; Eko Ahmad Riyanto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
In today's digital era, there are many educational video contents about UTBK that can be accessed through various social media platforms. Each video is expected to be useful for students in preparing for the Computer-Based Written Test (UTBK). This study aims to examine the types of speech acts, classify the forms of illocutionary speech acts in learning videos, and evaluate whether these speech acts are useful for students who will face UTBK. Illocutionary speech acts relate to the effect of data obtained by speech partners on an utterance that has been spoken from the speaker. This research uses descriptive qualitative research method to identify related data. The data results were obtained from nineteen “Siap UTBK 2023” videos in the Ruangguru playlist, using the listening and note-taking technique. Researchers watched educational videos about UTBK in Ruangguru playlist, then recorded and recorded statements that contained illocutionary speech acts. This research uses data analysis method in the form of agih technique to evaluate the type and form of illocutionary speech. Based on the data analysis, it can be found that there are assertive speech acts, directive speech acts, declarative speech acts, commissive speech acts, and expressive speech acts. Assertive speech acts can be in the form of stating, directive speech acts give prohibitions or orders, declarative speech acts give orders or form new perceptions, commissive speech acts promise or offer, while expressive speech acts contain hope or praise. Based on the results of the analysis in this study, the researcher hopes that it can deepen an understanding of illocutionary speech acts and how they are used, recognize the types of illocutionary speech acts, and convey directions to education and writers of UTBK learning materials to develop abilities in the learning process.